2020
DOI: 10.3390/ijms21062244
|View full text |Cite
|
Sign up to set email alerts
|

Complex Size and Surface Charge Determine Nucleic Acid Transfer by Fusogenic Liposomes

Abstract: Highly efficient, biocompatible, and fast nucleic acid delivery methods are essential for biomedical applications and research. At present, two main strategies are used to this end. In non-viral transfection liposome- or polymer-based formulations are used to transfer cargo into cells via endocytosis, whereas viral carriers enable direct nucleic acid delivery into the cell cytoplasm. Here, we introduce a new generation of liposomes for nucleic acid delivery, which immediately fuse with the cellular plasma memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…For example, some researchers combined fusogenic lipids (DMPC) with solid porous silicon nanoparticles (pSiNP) cores, loaded siRNA into pSiNPs via calcium ion precipitation, and showed that the uptake mechanism could be engineered to be independent of common receptor-mediated endocytosis pathways [ 170 ]. Marco et al [ 171 ] also analyzed the composition and proportion of lipids and concluded that factors such as surface charge and particle size would affect the occurrence of membrane fusion, thus affecting the transfer of various nucleic acids. Since most membrane fusion is mainly a process driven by physicochemical properties of particles and plasm membrane, the fusion efficiency is basically irrelevant to cell types.…”
Section: Synthetic Non-viral Vectors For Rna Deliverymentioning
confidence: 99%
“…For example, some researchers combined fusogenic lipids (DMPC) with solid porous silicon nanoparticles (pSiNP) cores, loaded siRNA into pSiNPs via calcium ion precipitation, and showed that the uptake mechanism could be engineered to be independent of common receptor-mediated endocytosis pathways [ 170 ]. Marco et al [ 171 ] also analyzed the composition and proportion of lipids and concluded that factors such as surface charge and particle size would affect the occurrence of membrane fusion, thus affecting the transfer of various nucleic acids. Since most membrane fusion is mainly a process driven by physicochemical properties of particles and plasm membrane, the fusion efficiency is basically irrelevant to cell types.…”
Section: Synthetic Non-viral Vectors For Rna Deliverymentioning
confidence: 99%
“…Therefore, liposomes as three-dimensional spherical structures that encapsulate hydrophilic or hydrophobic molecules can enter cells by endocytosis [ 70 ]. When a liposome is positively charged, DNA and RNA can form strong bonds through electrostatic attraction, adsorbing them on the surface of liposome [ 71 ], which efficiently protects the nucleic acid from degradation. Currently, commercial cationic liposomes and lipofection kits are available for the delivery of RNAi gene and plasmid DNA (pDNA).…”
Section: Kinds Of Nps-based Crispr/cas9 Systemmentioning
confidence: 99%
“…Elsewhere, Fusogenic Liposomes (FLs) were prepared by fusing conventional liposomes with inactivated viruses. FLs delivered the content directly to the cytoplasm without the drawback of cytotoxicity, hence emerged as a powerful tool for gene delivery systems [111,112] . However, it is recently shown that NATs have set foot in clinical applications after overcoming limitations of limited cellular uptake, low biological stability and offtarget effect.…”
Section: Delivery Of Nucleic Acid Therapeu-tics and Imagingmentioning
confidence: 99%